Do strong family ties inhibit trust? - John Ermisch; Diego Gambetta (University of Essex, Institute for Social and Economic Research (ISER), 2008)
We provide direct evidence that people with strong family ties have a lower level of trust in strangers than people with weak family ties, and argue that this association is causal. We also investigate the mechanisms that underlie this effect, and provide evidence that these revolve around the level of outward exposure: factors that limit exposure limit subjects experience as well as motivation to deal with strangers. Our findings are based on experimental data derived from a new design of the trust game combined with panel survey data, both drawn from a near-representative sample of the British population.
Keywords: 330